Treating the body to prevent brain injury: lessons learned from the coronavirus disease 2019 pandemic. Issue 2 (19th April 2022) - Fan, Tracey H.; Solnicky, Veronika; Cho, Sung-Min
Abstract : Purpose of review: We aim to provide the current evidence on utility and application of neuromonitoring tools including electroencephalography (EEG), transcranial Doppler (TCD), pupillometry, optic nerve sheath diameter (ONSD), cerebral near-infrared spectroscopy (cNIRS), somatosensory-evoked potentials (SSEPs), and invasive intracranial monitoring in COVID-19. We also provide recent evidence on management strategy of COVID-19-associated neurological complications. Recent findings: Despite the common occurrence of neurological complications, we found limited use of standard neurologic monitoring in patients with COVID-19. No specific EEG pattern was identified in COVID-19. Frontal epileptic discharge was proposed to be a potential marker of COVID-19 encephalopathy. TCD, ONSD, and pupillometry can provide real-time data on intracranial pressure. Additionally, TCD may be useful for detection of acute large vessel occlusions, abnormal cerebral hemodynamics, cerebral emboli, and evolving cerebral edema at bedside. cNIRS was under-utilized in COVID-19 population and there are ongoing studies to investigate whether cerebral oxygenation could be a more useful parameter than peripheral oxygen saturation to guide clinical titration of permissive hypoxemia. Limited data exists on SSEPs and invasive intracranial monitoring. Summary: Early recognition using standardized neuromonitoring and timely intervention is important to reduce morbidity and mortality. The management strategy for neurological complications is similar to those without COVID-19.